2020
DOI: 10.3390/membranes10060134
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Poly(Acrylic) Acid-Modified Heterogenous Anion Exchange Membranes with Improved Monovalent Permselectivity for RED

Abstract: The performance of anion-exchange membranes (AEMs) in Reverse Electrodialysis is hampered by both presence of multivalent ions and fouling phenomena, thus leading to reduced net power density. Therefore, we propose a monolayer surface modification procedure to functionalize Ralex-AEMs with poly(acrylic) acid (PAA) in order to (i) render a monovalent permselectivity, and (ii) minimize organic fouling. Membrane surface modification was carried out by putting heterogeneous AEMs in contact with a PAA-based aqueous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Dip coating is the process of immersing a membrane during a controlled period of time into a solution containing a modifying agent, to create an additional layer with desirable characteristics onto the surface of the membrane [53,54]. In a different approach, the solution used can also be in direct contact with only one side of the membrane, using two-compartment cells, in order to prepare one-side monolayer modifications [55], as represented in Figure 4. The importance of optimizing the modification conditions (i.e., immersion time and modifier concentration) as well as selecting the appropriate modifying agent to obtain a stable anionic polyelectrolyte layer on the surface of different Neosepta AEMs was discussed and demonstrated in 1995 [56], when two different anionic polyelectrolytes, namely a polycondensation product of sodium naphthalene and formaldehyde, and polystyrene sulfonic acids, respectively, were considered.…”
Section: Dip Coating Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Dip coating is the process of immersing a membrane during a controlled period of time into a solution containing a modifying agent, to create an additional layer with desirable characteristics onto the surface of the membrane [53,54]. In a different approach, the solution used can also be in direct contact with only one side of the membrane, using two-compartment cells, in order to prepare one-side monolayer modifications [55], as represented in Figure 4. The importance of optimizing the modification conditions (i.e., immersion time and modifier concentration) as well as selecting the appropriate modifying agent to obtain a stable anionic polyelectrolyte layer on the surface of different Neosepta AEMs was discussed and demonstrated in 1995 [56], when two different anionic polyelectrolytes, namely a polycondensation product of sodium naphthalene and formaldehyde, and polystyrene sulfonic acids, respectively, were considered.…”
Section: Dip Coating Strategiesmentioning
confidence: 99%
“…In particular, heterogeneous Ralex AEMs were modified by direct contact (during 24 h) with poly(acrylic) acid (PAA)-based solutions, which represents the use of a non-toxic and stable modifying agent [59,60]. The authors reported an improved surface hydrophilicity and monovalent membrane permselectivity as a function of different concentrations of PAA, without compromising the membrane electro-resistance [55].…”
Section: Dip Coating Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrochemical impedance spectroscopy (EIS) is increasingly being used to study IEM fouling [ 26 , 27 , 28 , 29 , 30 , 31 ]. The method of equivalent electrical circuits (EEC) is most often applied for the interpretation of experimental spectra [ 28 , 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy (EIS) is increasingly being used to study IEM fouling [ 26 , 27 , 28 , 29 , 30 , 31 ]. The method of equivalent electrical circuits (EEC) is most often applied for the interpretation of experimental spectra [ 28 , 29 , 30 , 31 ]. For example, an increase in the ohmic resistance of a membrane, which is determined by processing a high-frequency EIS arc using the EEC method, is the basis for online registration of the effect of fouling on the transport characteristics of membranes in reverse and conventional ED [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%